The Effect of Economic Growth and Foreign Direct Investment on Unemployment - Bojang, Sainey A.; Suliswanto, Muhammad Sri Wahyudi (International Journal of Social Science and Business, 2024)
This study aims to investigate the problem of failed employment growth in The Gambia that is not in line with the increase in the country's workforce, particularly related to the high speed of college graduates entering the workforce. The study is a quantitative study using annual time-series data from 1990 to 2021 from The Gambia, with datasets that include variables such as GDP growth, foreign direct investment, and unemployment rates. The data was extracted from the World Bank database and analyzed using the E-views statistical package. This study used augmented Dickey-Fuller unit root tests and autoregressive distributed lag (ARDL) models against existing data sets. The results showed that there was no long-term correlation between the variables studied. In particular, in the short term, economic growth has a negative and insignificant influence on the unemployment rate in The Gambia, while foreign direct investment has a positive and significant impact. The implications of this study suggest that the Gambian government needs to maintain budget restrictions and allocate planned expenditures to meet the infrastructure development needed for businesses to thrive. The Gambia is also advised to attract greenfield investment to create new jobs, by encouraging foreign investors to get involved in sectors of the country's native economy, including the agricultural and manufacturing industries.